Efforts to Enhance Student Learning Outcomes on the Topics of Temperature and Heat through Mathematical Operations Practice - Yudistia Rachman, Fitriany; U.S, Supardi; Hopeman, Teofilus Ardian (Nusa Putra University, 2024)
This study aims to improve the learning outcomes of seventh-grade students on the science topic of temperature and heat by incorporating mathematical operations practice at SMP Unggulan Ar Rahman. This research is a classroom action study, involving stages of planning, implementation, observation, and reflection, conducted during the even semester of the 2020/2021 academic year. The research subjects were 12 seventh-grade students. Data sources included both quantitative and qualitative data. The primary research instruments were the researcher’s observations and field notes for qualitative data, and evaluation questions for quantitative data. Data analysis employed both qualitative and quantitative methods. The results indicated an improvement in students’ learning outcomes, beginning with 71.67% in Cycle I, increasing to 80.45% in Cycle II, and reaching 89.58% in Cycle III. These findings suggest that practicing mathematical operations outside of regular science class time can enhance student comprehension and performance on the topic of temperature and heat.